Implementation Screening Program of the “Prevention of Mother to Child Transmission of HIV” (PMTCT) by Midwives in Health Center at Sorong West Papua. - Elisabeth Samaran; Zahroh Shaluhiyah; Ayun Sriatmi (Jurnal Manajemen Kesehatan Indonesia, 2013)
Berdasar data DKK Sorong 2010, dari total wanita penderita HIV/AIDS, 83,5% wanita usia reproduktif, yang sebagian besar tertular dari suami. Ketika hamil, terjadi resiko penularan HIV pada bayi. DKK Sorong telah melaksanakan program PMTCT dan memberikan pelatihan VCT-PMTCT pada tenaga kesehatan di puskesmas. Jumlah ibu hamil yang berkunjung ke klinik ANC-PMTCT sebanyak 2325 ibu hamil. Dari jumlah tersebut yang mendapat konseling pra-tes 1.171 ibu (50,36%). Dari yang mendapat konseling pra-tes dan melakukan tes HIV1.005 ibu (85,82%) dan ditemukan serologis positif HIV sebanyak 20 ibu (1,99%). Tujuan penelitian menjelaskan implementasi programPMTCT) di puskesmas.Jenis penelitian deskriptif dengan metode kualitatif. Pengumpulan data menggunakan wawancara mendalam pada informan utama bidan koordinator puskesmas dan informan triangulasi adalah Kepala Puskesmas, Kasie KIA dan Kasie Yankes DKK, sedangkan pada ibu hamil, data dikumpulkan melalui FGD.Hasil penelitian menunjukkan bahwa sosialisasi PMTCT telah dilakukan DKK melalui pelatihan dan kunjungan lapangan. Bidan juga melakukan sosialisasi pada ibu hamil yang pertama kali berkunjung untuk periksa hamil. Sosialisasi secara verbal dengan penyuluhan dan berkelompok. Bidan dari puskesmas yang program PMTCT baik telah melakukan langkah konseling pre-tes, testing HIV dan konseling post-test. Pada puskesmas yang program PMTCT tidak berjalan, bidan hanya menjelaskan manfaat PMTCT tetapi tidak pernah menyarankan untuk melakukan test darah. Pengetahuan dan sikap bidan sudah baik terutama dalam memberikan penyuluhan, sosialisasi dan informasi tentang HIV/AIDS dan PMTCT. Jumlah tenaga terlatih PMTCT dan sarana prasarana terbatas, terutama ruang khusus konseling serta laboratorium. Tidak ada regulasi khusus terkait PMTCT kecuali Pedoman Nasional PMTCT yang dikeluarkan oleh Kemenkes. Ada SK tentang puskesmas PMTCT dan pelaksanaannya menggunakan pedoman alur yang dibuat puskesmas berdasarkan kesepakatan dengan DKK. Dukungan pimpinan dan rekan sejawat dalam PMTCT di puskesmas baik.DKK perlu mengalokasikan anggaran secara bertahap untuk pelatihan PMTCT bagi bidan yang belum dilatih dan melengkapi sarana prasarana yang dibutuhkan terutama ruang khusus konseling dan laboratorium. Perlu reward yang dapat memotivasi bidan dan pembinaan yang terjadwal rutin. Based on Sorong city health office (DKK) data in 2010, 83.5% women with HIV/AIDS were in the productive age group, and the majority of them were transmitted from their husbands. Risk of HIV transmission to a baby occurred during pregnancy. DKK Sorong had implemented PMTCT program and given VCT-PMTCT training to health workers of primary healthcare centers. The number of pregnant women visited ANC-PMTCT clinic was 2325 women. Among them, 1.171 (50.36%) received pre testing counseling. Among women who received pre-testing counseling, 1.005 women conducted HIV1 test, and positive HIV was found in 20 women (1.99%). Objective of this study was to explain the implementation of PMTCT in the primary healthcare center (puskesmas). This was a descriptive study using qualitative method. Data were collected through in-depth interview to main informants and triangulation informants. Main informant was coordinator midwives in the puskesmas. Triangulation informants were heads of puskesmas, a head of KIA section of DKK, a head of Health Service section of DKK, and pregnant women. Data from pregnant women were collected through focus group discussion.  Results of the study showed that PMTCT socialization had been done by DKK through trainings and field visits. Midwives had done socialization to pregnant women who conducted antenatal visit for the first time. Verbal socialization was conducted by giving education, and it was done in groups. Midwives from puskesmas with good PMTCT had conducted pre-test counseling, HIV testing, and post-test counseling. In the puskesmas with improper PMTCT program, midwives only explained the benefit of conducting PMTCT; they did not suggest pregnant women to do blood test. Knowledge and attitude of midwives were sufficient specifically when they gave education, socialization, and information about HIV/AIDS and PMTCT. The number of skilled workers on PMTCT and facilities were limited; specific limitation on facilities was on the availability of specific rooms for counseling and laboratory. No specific regulations related to PMTCT except National guideline on PMTCT issued by Ministry of Health was provided. There was a decree regarding PMTCT puskesmas; the implementation of this decree was done by using flowchart guideline made by puskesmas with the agreement from DKK. Support for PMTCT from the leader and colleague in the puskesmas was good. Suggestions for DKK are to allocate the budged, in stages, for PMTCT trainings for midwives who have not received training, to complete facilities especially specific rooms for counseling and laboratory. Rewards that motivate midwives and routine scheduled supervision are required.